Conformational distributions of helical perfluoroalkyl substances and impacts on stability. Issue 24 (23rd July 2022) - Mifkovic, Maleigh; Van Hoomissen, Daniel J.; Vyas, Shubham
Abstract: Per‐ and polyfluoroalkyl substances (PFAS) have been widely used the past 70 years in numerous applications due to their chemical and thermal stability. Due to their robust stability, they are environmentally recalcitrant which made them one of the most persistent environmental contaminants. In addition to strong CF bond strength, oleophobicity, hydrophobicity, and high reduction–oxidation (redox) potential of PFAS has led to their inefficient degradation by traditional means. A characteristic of their structure is also their preference to adopt helical conformations along the carbon backbone, contrary to their hydrocarbon analogues. This work investigates the helical nature of perfluoroalkanes through their conformational distributions, especially as a benchmark for determining the impact of polar head groups, heteroatoms, and radical center on helical conformations. Since structure governs reactivity and molecular properties, it is important to assess if minor chemical perturbations in the structure will lead to changes in the conformations. Based on density functional theory calculations and comprehensive conformational distributions, it was concluded that the helicity is a local structural property which changes significantly with the presence of heteroatoms in the perfluoroalkyl chain as well as with the presence of radical centers. Abstract :